TALES OF THE ‘ORTHODOX NATION’ AND ‘MACEDONIAN FAITH’ EASTER AT MACEDONIANS IN PORECHE IN SCOPE OF REGIME, ETHNIC AND SOCIAL CHANGES IN THE REPUBLIC OF MACEDONIA (ЕтноАнтропоЗум, 2015)
This paper is based on my fieldwork in Poreche Region (Republic of Macedonia), in 2010, 2011, 2013 and 2014. My research focused on the meaning of the Easter holiday for the local community in Makedonski Brod during Macedonian post-communism transformation and also during transition from Yugoslav to an independent state. In a difficult period of transition and under real threat to Macedonians’ subjectivity (by Greeks, Bulgarians and some Albanian groups, see also not-recognition autocephaly of Macedonian Orthodox Church by Serbian and other Orthodox Churches), regular meetings,rituals, talks, storytelling and common fun strengthen local identity. They integrate community and ease people’s concerns about their future and (their?) country. Religionhere is ‘code of meanings’ and it builds social cohesiveness, it’s also – as I observed – the ‘memory’ of local communities and the nation (see Hervieu-Leger’s theory). Rituals and others symbolic practices of the Holy Week period (such as gathering, processions, Towerskuli play etc.) are part of social performance, during which residents of Makedonski Brod remember, (re)build, present and play (perform) their own identity and knowledge about the past of the community. National and local identities are constructed on the basis of Christian religion, territory of town and region, Macedonian language (especially local dialect), and various specific habits and customs. For local people Christianity is not only religion, but national identity (“our Macedonian religion”, “our Orthodox Christian nation”), and it’s opposite, the “Turkish religion”, synonymous of Islam, represented these days by Others - Albanians from Kosovo and Macedonia and especially by radical political Islamic groups (it’s important to say that other Albanian and Islamic groups - especially the Bektashi order - are not seen as dangerous. There is cohabitation and understanding between them and the Orthodox Macedonians, for example during the festival of St George in Makedonski Brod).This article discusses symbolic practices, repeated year after year during Easter by the Macedonians from Makedonski Brod in Poreche. It shows how this holiday preserves the whole community, its identity and territory as well as putting  symbolic order into people’s everyday life.